Peran Kepemimpinan Pelayan Pembelajaran Kepala Sekolah Berbasis Nilai-Nilai Moral Spiritual - Effendi, Yulius Rustan; Romadhon, Romadhon (QUALITY, 2023)
The Learning Servant Leadership Role of Principals Based on Moral-Spiritual Values. This research aims to provide an objective description of the role of the principal as a learning servant leader based on spiritual and moral values. The implementation of learning servant leadership in two junior high schools in Malang City, East Java is also examined. A case study approach was employed using qualitative methods to collect data through in-depth interviews, observations, and document analysis. A modified analytic analysis method was utilised to analyse the data and achieve research objectives. A modified analytic analysis method was utilised to analyse the data and achieve research objectives. Technical terms are explained when first used, and the language used is formal and value-neutral with clear, concise sentences and a logical flow of information. The validity of the data is measured using processes of credibility, transferability, dependability, and confirmability. According to the study's findings, the principal's objective is to enhance and empower the teaching potential of the educators for achieving restoration of learning. Self-awareness as an altruist, faithful (spiritual) and moral individual is the foundation of inspiration for the principal's role as a learning leader. This study suggests that the acquisition of servant leadership by principals has a subordinate effect on institutional or organizational outcomes while having a direct impact on investing in developing teachers' teaching potential for future learning recovery. Furthermore, the leadership of the principal's learning servant is highly appropriate for aiding teachers in their recovery and personal development. The approach prioritises the psychological well-being, emotional maturity, and ethical, moral, and religious wisdom of those being served, which is of great benefit to educators. Kepemimpinan pelayan pembelajaran kepala sekolah merupakan strategi peran kepemimpinan yang mengintegrasikan semangat pelayanan dengan nilai-nilai moral spiritual. Penelitian ini bertujuan untuk mendeskripsikan peran kepemimpinan pelayan pembelajaran kepala sekolah berbasis nilai-nilai moral spiritual. Kepemimpinan pelayan pembelajaran diterapkan oleh dua kepala Sekolah Menengah Pertama di Kota Malang, Jawa Timur berbasis nilai-nilai moral spiritual. Penelitian ini menggunakan pendekatan kualitatif, desain studi kasus. Pengumpulan data melalui wawancara mendalam, observasi, dan studi dokumentasi untuk mencapai tujuan penelitian. Analisis data menggunakan metode analisis analitik yang dimodifikasi. Pengukuran keabsahan data berdasarkan proses kredibilitas, transferabilitas, ketergantungan, dan konfirmabilitas. Hasil penelitian menjelaskan bahwa. tekad kepala sekolah adalah mengungkit dan memberdayakan potensi pengajaran guru untuk mencapai pemulihan pembelajaran. Sumber inspirasi peran kepemimpinan pembelajaran kepala sekolah berpusat pada kesadaran diri sebagai pribadi altruis, beriman (spiritual) dan bermoral. Penelitian ini merekomendasikan bahwa kepemimpinan pelayan pembelajaran kepala sekolah berpengaruh tidak langsung pada hasil organisasi/lembaga, tetapi berdampak langsung pada investasi pemberdayaan potensi pengajaran guru untuk mencapai pemulihan pembelajaran di masa depan. Selain itu, kepemimpinan pelayan pembelajaran kepala sekolah sangat cocok untuk pemulihan dan penyadaran pribadi guru karena terfokus pada kesejahteraan psikologis, kematangan emosional, dan kebijaksanaan etis, moral, religius dari individu yang dilayani.